Pengaruh Media Sosial Instagram Terhadap Minat Beli Konsumen Pada Industri Socolatte Di Desa Baroh Musa Kecamatan Bandar Baru Kabupaten Pidie Jaya - Naya Desparita; Risna Diani; T.M. Nur (Journal of Agribusiness, Social and Economic, 2025)
The development of digital technology, especially social media, has had a significant impact on the marketing strategies of small and medium enterprises. This study aims to analyze the effect of the use of Instagram social media on consumer purchasing interest in the Socolatte industry in Baroh Musa Village, Bandar Baru District, Pidie Jaya Regency. The research method used is quantitative with a simple linear regression analysis technique. Data were obtained by distributing questionnaires to 100 respondents who were followers of the Socolatte Instagram account.The results of the study indicate that Instagram social media has a positive and significant effect on consumer purchasing interest. This is evidenced by the coefficient of determination (R²) value of 64.9%, which indicates that the Instagram social media variable is able to explain 64.9% of the variation in consumer purchasing interest, while it is influenced by other factors. Factors such as ease of access, quality of information, and interaction through Instagram are the main factors in attracting consumer purchasing interest.This study gives the impression for the Socolatte industry and other business actors to further maximize marketing strategies through social media, especially Instagram, in order to increase consumer appeal and trust in the products offered.